The Simple View of Personal Identity (in Polish) - Grygianiec, Mariusz (Diametros, 2018)
In the debate on personal identity, different criteria of identity are proposed and defended. The criteria of identity have usually been taken to state the necessary and sufficient conditions of identity and are interpreted as providing truth conditions for relevant identity statements. The Simple View of personal identity is the thesis that there are no noncircular and informative metaphysical criteria of identity for persons. The paper intends to first deliver a precise and general formulation of the Simple View, and, second, to present the various arguments in favour of the doctrine in question. It argues that there are no other facts of the matter than identity itself which could serve as the truth-conditions of identity statements. The considerations presented in the paper lead to the conclusion that, although the Simple View is faced with many theoretical difficulties, it is still a lively intellectual position in the debate on personal identity.